(untitled) (Collaborate Engineering Daily Book Series, 2025)
Lean Manufacturing is a production management approach that aims to increase efficiency and productivity by reducing waste and adding value at every stage of the production process. This study aims to analyze the application of Lean Manufacturing in XYZ manufacturing companies and assess its impact on production performance. The research method uses case studies with a descriptive approach, which combines quantitative data in the form of productivity measurements, lead time, and production costs, as well as qualitative data through direct observation and interviews with managers and production staff. The results show that the implementation of Lean principles, such as 5S, Kaizen, Just-In-Time (JIT), and Kanban, provides a significant improvement in production efficiency; The work area becomes more organized, workflow is smoother, lead time is reduced, material waste decreases, and labor productivity increases. The study also found challenges in implementation, including employee resistance to change and the need for continuous training. In conclusion, Lean Manufacturing has proven to be effective in improving efficiency, productivity, and product quality, as well as being an important strategy to strengthen the company’s competitiveness. This study recommends the continuous implementation of Lean, supported by integration with digital technology for real-time monitoring and more optimal process improvement.